A new solution method for fuzzy chance constrained programming problem - Nanda, S.; Panda, G.; Dash, J. K. (Fuzzy optimization and decision making, 2006)
This paper deals with an optimization model, where both fuzziness and randomness occur under one roof. The concept of fuzzy random variable (FRV), mean and variance of FRV is used in the model. In particular, the methodology is developed in the presence of FRV in the constraint. The methodology is verified through numerical examples. [PUBLICATION ABSTRACT]